2011
DOI: 10.1521/soco.2011.29.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Action for Agents with Varying Cognitive Capacities

Abstract: in this report, we investigated participants' beliefs about how different agents represent action. in Experiment 1, participants divided actions into units for two hypothetical observers. Participants marked fewer units for a person than for either of two different machine agents, suggesting that motions were integrated into larger goal-based units for the human but not for the machines. An analysis of alignment between participant breakpoints and coded action features demonstrated that participants selected l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The relevance of camera viewpoint for learning was included because of the numerous reports that have shown that individuals who play first-person perspective “shooter” games, but not other games, demonstrate improvement on certain visual cognitive tasks (e.g., Feng, Spence, & Pratt, 2007 ; Green & Bavelier, 2006 , 2007 ). Anthropomorphism was included because of numerous findings suggesting that anthropomorphic attributes affect a range of perceptual, cognitive, and social tasks (e.g., Heider & Simmel, 1944 ; Killingsworth, Levin, & Saylor, 2011 ; Mahajan & Woodward, 2009 ).…”
Section: Moderator Analyses Of Visual and Narrative Game Characteristmentioning
confidence: 99%
“…The relevance of camera viewpoint for learning was included because of the numerous reports that have shown that individuals who play first-person perspective “shooter” games, but not other games, demonstrate improvement on certain visual cognitive tasks (e.g., Feng, Spence, & Pratt, 2007 ; Green & Bavelier, 2006 , 2007 ). Anthropomorphism was included because of numerous findings suggesting that anthropomorphic attributes affect a range of perceptual, cognitive, and social tasks (e.g., Heider & Simmel, 1944 ; Killingsworth, Levin, & Saylor, 2011 ; Mahajan & Woodward, 2009 ).…”
Section: Moderator Analyses Of Visual and Narrative Game Characteristmentioning
confidence: 99%